Taberna 1 from Mirobriga (Santiago do Cacém, Portugal): ceramic evolution of the Late Antique levels - Carlos Quaresma, José; Banha da Silva, Rodrigo; Guimarães, Raquel; Sousa, Filipe; Felício, Catarina (Rei Cretariae Romanae Fautorum Acta, 2022)
The aim of this article is to introduce a methodological approach to the study of Late Antique contexts and ceramics in the Iberian Atlantic area. We present the example of the Roman town of Mirobriga, located in the southern area of Lusitania, near the Atlantic coastline, a middle-sized settlement, with an ongoing occupation in the Roman and Late Antique periods. The recent project of the excavation of its market sector allowed the identification of the last circulation levels in taberna 1, as detailed here, related to Late Antique/post-Roman phases of occupation. The imported and local typologies of these phases constitute important indicators of change, concerning typologies and fabrics, and the contribution of both to our knowledge of the transition between so-called Roman and post-Roman models.